Odpowiedzi

2009-12-07T17:30:41+01:00
A)x+2y = -2


2x-y=1

x=-2-2y
2(-2-2y)-y=1

x=-2-2y
-4-4y-y=1

-5y=5 //:5
y=1

x+2 = -2
x=0

x=0
y=1
2009-12-07T17:40:28+01:00
B.)
x+4y=-2
3x-8y=10

x=-2-4y
3(-2-4y)-8y=10

x=-2-4y
-6-12y-8y=10

x=-2-4y
-20y=4 /: (-20)

x=-2-4*(-0,2)
y=(-0,2)

x=(-1,2)
y=(-0,2)
Najlepsza Odpowiedź!
2009-12-07T17:47:06+01:00
A) x+2y=-2
2x-y=1
x=-2-2y
2*(-2-2y)-y=1
-4-4y-y=1
-5y=1+4
-5y=5
y=-1
x=-2-2*(-1)
x=-2+2
x=0

B) x+4y=-2
3x-8y=10
x=-2-4y
3*(-2-4y)-8y=10
-6-12y-8y=10
-20y=10+6
-20y=16
y=-16/20
y=-4/5
x=-2-4*(-4/5)
x=-2+16/5
x=6/5

C) x-2y=3
-2x+y=0
x=3+2y
-2*(3+2y)+y=0
-6-4y+y=0
-3y=6
y=-2
x=3+2y
x=3+2*(-2)
x=3-4
x=-1

D) 2x+y=9
5x-4y=3
y=9-2x
5x-4*(9-2x)=3
5x-36+8x=3
13x=3+36
13x=39
x=3
y=9-2*3
y=9-6
y=3

e) 3x-2y=5
2x-y=4
y=-4+2x
3x-2*(-4+2x)=5
3x+8-4x=5
-x=-3
x=3
y=-4+2*3
y=2

f) 2x+9y=-9
-3x+3y=8
2x=-9-9y
x=-9/2-9/2y
-3*(-9/2-9/2y)+3y=8
27/2+27/2y+3y=8
27/2y+3y=8-27/2
33/2y=-9/2
y=-9/2*2/33
y=-9/33
y=-3/11
x=-9/2-9/2*(-3/11)
x=-9/2+27/22
x=-99/22+27/22
x=-72/22
x=-36/11

g) 2x+3y=4
8x-5y=-1
2x=4-3y
x=4-3/2y
8*(4-3/2y)-5y=-1
32-12y-5y=-1
-17y=-33
y=33/17
x=4-3/2*(33/17)
x=4-99/34
x=136/34-99/34
x=37/34

H) x-y=0
x+y+z=4
x+2y+3z=9
x=y
z=4-x-y
z=4-x-x
z=4-2x
x+2x+3*(4-2x)=9
3x+12-6x=9
-3x=-3
x=1
y=1
z=4-2*1
z=2